Establishing laboratory cultures and performing ecological and evolutionary experiments with the emerging model species Chironomus riparius. (17th January 2019) - Foucault, Quentin; Wieser, Andreas; Waldvogel, Ann‐Marie; Pfenninger, Markus
Abstract: Chironomus riparius is a well‐established model organism in various fields such as ecotoxicology and ecology, and therefore, environmental preferences, ecological interactions and metabolic traits are well‐studied. With the recent publication of a high‐quality draft genome, as well as different population genetic parameters such as mutation and recombination rate, the species can be used as an alternative to the Drosophila models in experimental population genomics or molecular ecology. To facilitate access to this promising experimental model species for a wider range of researchers, we describe experimental methods to first create and sustain long‐term cultures of C. riparius and then use them to perform repeatable and comparable experiments for various research questions.